Accuracy of carbohydrate‐deficient transferrin as a biomarker of chronic alcohol abuse during treatment for alcoholism. Issue 1 (13th April 2021) - Suzuki, Tatsuya; Eguchi, Akiko; Shigefuku, Ryuta; Nagao, Saeko; Morikawa, Masayuki; Sugimoto, Kazushi; Iwasa, Motoh; Takei, Yoshiyuki
Abstract: Aim: Clinical evaluations are generally used to verify the effectiveness of detoxification treatments for alcohol dependence, but new objective biomarkers are essential for accurate diagnosis. We aim to assess the accuracy of carbohydrate‐deficient transferrin (%CDT) in a cohort of Japanese patients admitted to a psychiatric hospital specializing in alcohol dependence. In addition, we investigated the kinetics of %CDT during alcohol moderation or cessation. Methods: The study cohort consisted of 126 alcohol‐dependent patients. The levels of serum %CDT were assessed by the N Latex CDT direct immunonephelometric assay. Results: Alcohol consumption was significantly correlated with %CDT. The only independent predictive factor of alcohol consumption was %CDT, with glutamyltranspeptidase (GGT) and albumin–bilirubin score proving insufficient. The cut‐off value of %CDT was 1.9% with high sensitivity and specificity in detecting alcohol abstinence beyond 30 days (68.6% sensitivity, 91.8% specificity) and excessive alcohol drinking (77.9% sensitivity, 77.1% specificity). The %CDT levels were significantly decreased at 30 days of abstinence when compared with baseline. Notably, %CDT values were significantly changed even in the light alcohol drinking cohort ( p  = 0.0009), whereas GGT levels were not significantly changed. Conclusions: Our results indicate that %CDT is an accurate and specific biomarker of alcohol consumption and is useful in detecting alcohol abstinence even in a low alcohol intake patient cohort. These results suggest that %CDT could be a useful objective biomarker of chronic alcohol abuse during clinical treatment for alcoholism.